Pengaruh Good Corporate Governance, Likuiditas, Struktur Modal terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Pertambangan Oil dan Production yang Terdaftar di Bursa Efek Indonesia, Periode 2020-2024 - Nelasarih Lumbantobing; Rismawandi Rismawandi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the influence of Good Corporate Governance (GCG), liquidity, and capital structure on the performance of mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Company performance in this research is measured using the Net Profit Margin (NPM) as an indicator of profitability. GCG is proxied through two variables, namely managerial ownership and the existence of an audit committee. Liquidity is measured by the current ratio, while capital structure is assessed using the debt-to-asset ratio (DAR). This research employs a quantitative approach with multiple linear regression analysis. The data were obtained from annual financial reports of mining companies selected through purposive sampling to ensure that the sample met the research criteria. The findings reveal that GCG, as represented by managerial ownership, does not have a significant effect on company performance, whereas the existence of an audit committee has a positive and significant impact on performance improvement. Furthermore, liquidity does not significantly affect company performance, suggesting that the availability of current assets does not always translate into higher profitability. On the other hand, capital structure demonstrates a significant influence on company performance, highlighting the crucial role of effective capital structure management in sustaining and enhancing financial performance. These results provide practical implications for corporate management in formulating financial policies, for investors in evaluating company prospects, and for regulators in developing policies that foster better corporate governance practices within the mining sector.